The possible effect of stratospheric quasi-biennial oscillation on the critical frequency of the ionospheric F2-layer - Sagir, S.; Atici, R.; Ozcan, O. (Indian Acad Sciences, 2018)
In this study, the coupling between the stratospheric quasi-biennial oscillation (QBO) and the critical frequency of the ionospheric F2-layer (foF2) was analysed statistically. The multiple regression model was used as a statistical tool. The model was developed by adding the sunspot number (SSN), which affects the foF2 (measured for Madras, Kodaikanal, Bogota, Manila and Tahiti) in the ionosphere at a significant level. Four different 'Dummy' sets of data were used in the model in order to observe the effect of the direction (east-west) and the magnitude (for both directions, between 0 and 15 m / s and between 0 and 16 m / s and the largest value) of QBO. It was observed that the variations of foF2 in the range of 60-78% in the model could be explained by SSN and . The change of 2-13% that occurred in foF2 could be explained by the whole set of QBO. It was also observed that the effect of the direction and magnitude of QBO on foF2 differed between the stations.
Keywords: Ionospheric critical frequency; quasi-biennial oscillation; sunspot number; multiple regression model